PENGARUH KUALITAS PELAYANAN, HARGA, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PENGGUNAAN JASA CLEAN YOUR SHOES - Vera Fadhilah Priyono; Handoyo Djoko Waloejo (Universitas Diponegoro, 2019)
Nowadays there a lot of new businesses that offering services, one of them is washing shoes sevices. Today's shoe washing services are much more modern. This business exists, is inseparable from the consumptive nature of the society for his interest in the type of kats or sneakers. Seeing the enthusiasm of the community for their interest in caring for shoes, it makes a business opportunity for business people to start businesses in this field. Clean Your Shoes is a pioneer in shoes care and washing services in Semarang. There are several factors that influence the choice of consumers to buy a service, including service quality, price, and word of mouth. This study aims to determine the effect of service quality, price, and word of mouth on the decision to use Clean Your Shoes services (case study on service users of Clean Your Shoes in Tembalang, Semarang). This type of research is explanatory research. The sampling techniques used are incidental sampling and purposive sampling. The number of samples taken was 100 respondents, who are users of Clean Your Shoes Tembalang, Semarang. The research that is used to determine the effect of service quality and price on purchase decisions will present statistics with the help of IBM SPSS version 21.0. The result of this research shows that service quality affected the decision to use services by contributing 57.1%, price affects the decision on the use of services by contributing 43.2%, and word of mouth affects the decision for the use of services by contributing 34.2%. Whereas, service quality, price, and word of mouth simultaneously influence the decision to use services by contributing 61.82%. While the rest is influenced by other factors besides service quality, price, and word of mouth. Based on the calculation of the F Test shows that there is a significant influence between service quality, price, and word of mouth on the decision to use the service.